Reputable Relevant Realistic Reliable and Rigorous Human Resource Management Strategic Approaches and Practices in the 21st century - Tayali, Esnart Mwaba; Sakyi, Kwesi Atta (Advances in Social Sciences Research Journal, 2020)
Human resource management is a multi-dimensional and complex phenomenon comprising a number of management themes. Without reputable, relevant, realistic, reliable and rigorous Human Resource Management strategic approaches and practices, companies can fail to effectively operate in a global market. The world has become interconnected as companies operate in a competitive global market economy. Even though Human Resource Management continuously gains scholarly attention yet there are still many gaps in it which need attention. There is no conclusive research on Human Resource Management strategies and approaches in the management of complex workplace issues. These complex issues faced today include convergence, divergence and cross-vergence of International Human Resource Management approaches, Cross-Cultural Management, Reward Strategy, Talent Management, and Control or Commitment Strategy. This paper provides a springboard for a better understanding of the Human Resource Management strategies, approaches and practices in the management of complex workplace issues. Appropriate management of people endows companies with unique and indispensable capabilities and capacities needed for differentiating and survival in a global market economy. The paramount goal of an organisation is to meet and satisfy customer needs and to be a market leader. Reputable, relevant, realistic, reliable and rigorous Human Resource Management strategies can help to fulfil the needs of customers, thereby increasing company profitability.